A Method for Dimensioning and Designing the Zero-Sequence Electromagnetic Blocker Considering System Unbalance Factor - Fonseca Buzo, Ricardo [UNESP]; Oliveira, Luis Carlos Origa de [UNESP]; Leao, Fabio Bertequini [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2020)
The zero-sequence electromagnetic suppressor (ZSES) refers to a well-established alternative during the zero-sequence current mitigation in industrial systems. Its arrangement consists of a zero-sequence electromagnetic filter (ZSEF) and a zero-sequence electromagnetic blocker (ZSEB). Since the ZSEB also plays an important role in the ZSES performance, this paper presents an extensive analysis showing the impacts that can be caused when the ZSEB operates under non-ideal condition. To circumvent such impacts, this paper proposes an innovative method for dimensioning and designing the ZSEB, allowing the ZSES performance to be conveniently adjusted. The proposed technique allows the user to know the current unbalance factor that will result in the supply system. Applying the proposed method, it is verified in the PSIM software that the ZSEB presents exactly the performance as adjusted.
Keywords: Dimensioning; designing; electromagnetic blocker; confinement; zero-sequence currents